2011
DOI: 10.1111/j.1745-4514.2010.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Acid Invertase Activity and Sugar Content in Grape Species

Abstract: Among grape species muscadines are the important grape crops of the southeastern United States,where cultivation of Vitis vinifera is limited due to Pierce's disease.Muscadine grapes are less desirable because of their low sugar content and leathery skin. Sugar accumulation in berry depends on the activity of sugar metabolizing enzymes during ripening. The present study was carried out to investigate differences in invertase activity among Muscadinia rotundifolia (Muscadine), Vitis spp. (Florida hybrid bunch) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Another reason may be that differences in the expression levels of sugar metabolizing genes among the genotypes may influence the sugar content in the grape berries. 20 Our previous studies showed lower invertase activity in muscadine genotypes compared with FHB and bunch grape cultivars, 21 confirming this observation.…”
Section: Discussionsupporting
confidence: 63%
“…Another reason may be that differences in the expression levels of sugar metabolizing genes among the genotypes may influence the sugar content in the grape berries. 20 Our previous studies showed lower invertase activity in muscadine genotypes compared with FHB and bunch grape cultivars, 21 confirming this observation.…”
Section: Discussionsupporting
confidence: 63%
“…Sugar accumulation is an important event in the berry-ripening physiology of grapevine, and is essential for superior enological characteristics and product value. 1 Also sugar content in grape berries is the major factor determining fruit quality. Sugar is synthesized in leaves as a result of photosynthesis and imported via the phloem into the berry in the form of sucrose.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar accumulation is an important event in the berry‐ripening physiology of grapevine, and is essential for superior enological characteristics and product value . Also sugar content in grape berries is the major factor determining fruit quality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metabolic activity continues as a result of fruit ripening, which leads to converting carbohydrates and organic acids into sugars to be used in several metabolic processes [58]. In our study, the increase of SSC in grapes with treatments and control grapes was due to conversion of sucrose into glucose and fructose [59]. Now, comparing with control grape, the NC-BCO-C and the NC-EOt-C multisystem showed lower values of SSC.…”
Section: Effect Of Nc-eot-c Multisystem On Postharvest Quality Andmentioning
confidence: 47%